Combining disturbance and competition to control creeping perennial weeds in a field study on three northern European sites - Weigel, Marian Malte; Berge, Therese With; Salonen, Jukka; Lötjönen, Timo; Gerowitt, Bärbel; Brandsæter, Lars Olav (Frontiers in Agronomy, 2024)
Controlling creeping perennial weeds is challenging throughout all farming systems. The present study distinguished and explored three different methods to control them non-chemically: Disturbance with inversion, disturbance without inversion and competition.Focusing on Cirsium arvense, Elymus repens and Sonchus arvensis, we conducted a field study (2019-2021) at three northern European sites in Germany, Finland and Norway. We investigated the effects of the control methods ploughing (inversion disturbance), root cutting (non-inversion disturbance) and cover crops (competition) alone. Root cutting was conducted using a prototype machine developed by "Kverneland". Eight treatments were tested in factorial designs adapted for each site. Control methods were applied solely and combined. Response variables after treatments were aboveground weed biomass and grain yield of spring cereals.The control method of ploughing was most effective in reducing weed biomass compared to root cutting or cover crops. However, compared to the untreated control, a pronounced additive effect of root cutting and cover crops occurred, reducing weed biomass (-57.5 %) similar to ploughing (-66 %). Pooled over sites, the response was species-specific, with each species showing a distinct reaction to both control methods. Cirsium arvense was most susceptible to root cutting, followed by E. repens, while S. arvensis showed no susceptibility. Crop yield losses were prevented compared to untreated plots by ploughing (+60.57 %) and root cutting (+30 %), but not by cover crops.We conclude that the combination of non-inversion disturbance and competition is a promising strategy to reduce the reliance on herbicides or inversion tillage in the management of perennial weeds.